Korelasi HbA1c, APTT dan PT Pada Pasien Diabetes Militus tipe 2 Sebagai Prediktor Hiperkoagulasi Di Rumah Sakit Umum Gambiran Kota Kediri - fathul hasanah; Anna Siga; Shela Sari (Jurnal Sintesis: Penelitian Sains, Terapan dan Analisisnya, 2021)
The state of chronic hyperglycemia in DM can cause an increase in blood clotting factor levels, these affect the hemostasis system, and become the basis for the emergence of a hypercoagulable state in DM patients, hypercoagulation can be identified by examination of clotting factors, these are PT and APTT. The purpose of this study was to determine the relationship between HbA1c, APTT, and PT in diabetes mellitus patients as a predictor of hypercoagulation. The design in this study uses a cross-sectional study. The population in this study were 108 DM patients at the Gambiran General Hospital, Kediri City with a total sample of 20 Type 2 Diabetes Mellitus patients, Sampling technique was purposive with inclusion criteria: type 2 DM patients with HbA1c levels > 6.4% and exclusion: Type I DM patients, Type 2 DM patients with anticoagulants treatment and type 2 DM patients with liver disease. The average HbA1c level was 9.35%, the maximum level was 14% and the minimum level was 6.5%. The average PT time was 12.6 seconds with the longest time being 14.9 seconds and the fastest time being 10.4 seconds. The results of the APTT examination have an average of 26.2 seconds with the longest time being 35.2 seconds and the fastest time being 22.7 seconds. HbA1c with APTT has no correlation, this is indicated by a p-value of 0.794 or > 0.05 and r = 0.062. HbA1c with PT there is a correlation with p-value 0.005 or <0.05 and a moderate level of correlation r = 0.598. The conclusion of this study, HbA1c in type 2 DM patients did not correlate with APTT, whereas have positively correlated with PT that it could be interpreted when HbA1c levels increased then the PT time would be prolonged or hypocoagulation